Do individual disposition and occupational self-efficacy work? Threat of COVID-19 on banks frontline employees’ performance: An emerging market context - Habib, Asmara; Dr. Muhammad Nazim; Mukhtar, Sana (Journal of Contemporary Business and Islamic Finance (JCBIF), 2022)
This study aims to analyze the divulgence of COVID-19 on individuals, institutions and institutional setups, evidence taken from banking sector of an emerging market of Pakistan. The study used, structured Questionnaire for the data collection purpose. The questionnaire was administered from the employees of banking sector of Pakistan. Total of 500 questionnaires were distributed having a 97% response rate. Analysis of the data was done using SPSS Process macro. Results show occupational self-efficacy positively affects the relationship of perceived threat of COVID-19 and employee performance. As the healthy work environment reduces the stress factor and helps in maximizing the performance outcome. Individual disposition further add the incremental factor as individual characteristics improve the employee performance specially and organizational performance generally. Current research provides input to the organizations like Banks; as to how they can minimize the perception of threat to improve the working of employees. It also provides useful human resource management practices to banking sector to control and decrease the effect of COVID-19 and such events. To the best of the author’s knowledge, this study is the ﬁrst attempt to analyze the divulgence of COVID-19 on individuals, institutions and institutional setups and therefore provides a signiﬁcant contribution to the occupational self-efficacy, individual disposition and COVID-19 literature.